A law on the end of life: emerging from ideological conflicts - Ciaccia, Romina; Fontana, Paolo (Medicina Historica, 2022)
After years of debates, the Chamber of Deputies approved in Italy the possibility of accepting, under certain conditions, to assisted suicide.The issue of physician-assisted suicide is considered among the most controversial of the current bioethical debates in our Country.Efforts are needed to overcome ideological extremisms, to welcome the different sensitivities that exist in the country and to reconcile the various options.